Two antibiotic combinations with and without Vitamin E or fermentation product in rations for growing pigs - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Growing pigs fed ASP-250 from birth to market gained equally as well as those fed TNT. Feed conversion values were quite similar. Adding a fermentation product or vitamin E to rations did not produce consistently better gains or feed efficiency.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Vitamin E; Fermentation; Rations; Antibiotic